Descriptive analysis of the successful cadets in the Philippine Military Academy - Duque, Benjamin C. 1928- (s.n.], 1964)
The kind of candidates that perform efficiently in the Philippine Military Academy was described in this study. The description of these cadets is focused on the following aspects: family and educational background, physical fitness, recreational and other social activities, career motivation, and scores in the American Council of Education Psychological Examination.